Family Trip to Sequoia National Park in 1924 Model T Ford - Watkins, Howard::::::::: (1978)
Family 1924 Model T Ford driving out of Tunnel Log Albert Watkins driving, Christine Watkins holding Adam Watkins, Rose Watkins